2022
DOI: 10.1111/jam.15489
|View full text |Cite
|
Sign up to set email alerts
|

The endophytic Aspergillus strains: A bountiful source of natural products

Abstract: Fungi that invade plant inner tissues without inducing disease symptoms are known as fungal endophytes. They represent a promising and tremendous reservoir of natural products with valuable biological potentials for application in medicine, agriculture and industry. Among the numerous existing endophytic fungi, Aspergillus strains constitute one of the most prolific sources of secondary metabolites with diverse chemical classes and interesting biological activities. This review covers the literature of the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
(42 reference statements)
0
9
0
1
Order By: Relevance
“…Aspergillus candidus, an endophyte, was isolated from the leaves of Pittosporum mannii and cultured with PDA and unpolished rice. Successive normal phase column chromatography used to fractionate and purify the ethyl acetate crude extract of A. candidus led to the isolation of eleven compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), among which an unparalleled unsaturated aliphatic anhydride derivative (Z)-(12Z)-heptadec-12-enoic-2′-hydroxypropanoic anhydride (1) as well as ten known compounds (2-11) (Figure 1). Compound (1) was obtained as a dextrorotatory ([a] 24 D � +0.89 (c 0.01; MeOH)) white amorphous powder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aspergillus candidus, an endophyte, was isolated from the leaves of Pittosporum mannii and cultured with PDA and unpolished rice. Successive normal phase column chromatography used to fractionate and purify the ethyl acetate crude extract of A. candidus led to the isolation of eleven compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), among which an unparalleled unsaturated aliphatic anhydride derivative (Z)-(12Z)-heptadec-12-enoic-2′-hydroxypropanoic anhydride (1) as well as ten known compounds (2-11) (Figure 1). Compound (1) was obtained as a dextrorotatory ([a] 24 D � +0.89 (c 0.01; MeOH)) white amorphous powder.…”
Section: Resultsmentioning
confidence: 99%
“…Figure S16-S17: 1 H-NMR and HMBC spectra of 5,4"-dihydroxy-7,8-dimethoxyfavone (4). Figure S18-S19: 1 H-NMR and 13 C-NMR spectra of 3hydroxyterphenyllin (6). Figure S20-S21: 1 H-NMR and 13 C-NMR spectra of 1,4-dimethoxy-2,4,"4″-trihydroxy-pterphenyllin (5).…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eurotiales mainly includes Aspergillus and Penicillium , which may produce terpenoids, polyketides, polysaccharides, esters, phenols, and organic acids. Endophytes of Aspergillus ( El-hawary et al, 2020 ; Hagag et al, 2022 ), Penicillium ( Marie et al, 2020 ), Fusarium ( Manoj and Anil, 2016 ; Marie and Toghueo, 2019 ), Drechmeria ( Liang et al, 2018 ; Yu et al, 2018 ; Zhao, J. et al, 2018b ), and Trichoderma ( Patel, J. et al, 2019 ) possess significant antibacterial, antifungal, antioxidant, anti-inflammatory, and anticancer activities.…”
Section: Endophytic Fungi Of Mfh Plants and Their Metabolitesmentioning
confidence: 99%
“…Endophytic fungi represent a promising and huge natural product pool with valuable biological potential for applications in medicine, agriculture, and industry . Among the numerous existing endophytic fungi, Aspergillus strains constitute one of the most prolific sources of secondary metabolites (SMs) with diverse chemical classes and interesting biological activities. , Whole genome sequencing has revealed that Aspergillus strains have the capacity to produce a far greater number of SMs than those that have been isolated. Prenylated indole alkaloids as hybrid natural products, derived from prenyl diphosphates and tryptophan or its precursors, have attracted widespread attention from chemists and biologists due to their diverse chemical structures and biological activities. , Among them, the fungal neurotoxin α-cyclopiazonic acid ( α -CPA), a nanomolar inhibitor of Ca 2+ -ATPase, has a pentacyclic indole tetramic acid scaffold and was first isolated from Penicillium cyclopium followed by many Penicillium and Aspergillus strains . In addition, a large number of CPA variations have been isolated in nature, involving indole or oxindole alkaloids of the tetramic acid unit, with attractive biological activities such as anti-TMV activity, , cytotoxicity, , antioxidant activity, , antibacterial activity, and other activity .…”
Section: Introductionmentioning
confidence: 99%